ON THE NATIONAL MARKING OF SOMATIC UTTERANCES (American Journal of Research in Humanities and Social Sciences, 2023)
It is known that somatic utterances in any language reflect aspects of culture and everyday life and are unique facts of the original historical development of a particular people. This article analyzes the lacunae - somatic utterances that exist in the modern Russian literary language.